Material Removal Rate and Diameter of overcut for Sodalime glass through pressurized flow ECDM Process for Mathematical Modelling by RSM CCD technique - Yugesh Kharche, Dr. Neeraj Kumar , Dr. Mukesh Gupta (International Journal of Advanced Science and Technology, 2020)
In this chapter a mathematical model that predicts overcut and material removal rate is presented. The model enables us to quantify the outcome of electrolyte concentration, voltage , duty factor and electrolyte flow rate on overcut and material removal rate in ECDM. It also aids in analyzing how the different machining parameters such as machining time, machining voltage and material properties affect the material removal. We understand that concentration of the electrolyte has an effect on the overcut. Only limited studies have been performed on the effect of concentration in the ECDM process as noticed in the literature review. Hence modeling the material removal is important in order to understand and improve the process capability.